Corporate Governance, Financial Performance, and Firm Value: Empirical Evidence from the Indonesian Energy Sector - Dermawan, Wildan Dwi; Desiana; Sanjayyana, Adzka Rosa (Universitas Pamulang, 2026)
This study aims to examine good corporate governance, financial performance, capital structure, good governance mechanisms, and company size in increasing the value of the energy sector in Indonesia. The method used is linear regression analysis with a purposive sampling technique. The sampel study for analysis from 26 energy companies from 2020 to 2024 amounts to 130 observations. The results of the study indicate that financial performance, debt-to-equity ratio, managerial performance, and independent commissioners significantly influence corporate value. However, company size and the independent board of commissioners do not affect firm value. This research shows that financial performance and good governance in the energy sector play a crucial role for management in managing and enhancing corporate value. This study will highlight the importance of the variables studied in managing corporate value in the energy sector using the latest and most up-to-date research data, thereby contributing to both practitioners and academics